Dead lawyers tell no tales - Singer, Randy (Randy D.) (Tyndale House Publishers, Inc., 2013)
"Landon Reed is an ex-quarterback convicted of organizing a points-shaving scheme. During his time in prison, he found forgiveness and faith and earned his law degree. Now he longs for an opportunity to prove his loyalty and worth. "Be careful what you ask for." Harry McNaughton is one of the founding partners of McNaughton & Clay--and the only lawyer willing to take a chance employing an ex-con-turned-lawyer. Though Landon initially questions Harry's ethics and methods, it's clear the crusty old lawyer has one of the most brilliant legal minds Landon has ever encountered. The two dive into preparing a defense for one of the highest-profile murder trials Virginia Beach has seen in decades when Harry is gunned down in what appears to be a random mugging. Then two more lawyers are killed when the firm's private jet crashes. Authorities suspect someone has a vendetta against McNaughton & Clay, leaving Landon and the remaining partner as the final targets. As Landon struggles to keep the firm together, he can't help but wonder, is the plot related to a shady case from McNaughton & Clay's past, or to the murder trial he's neck-deep in now? And will he survive long enough to find out?"--P. [2] of cover.